The effect of circuit training on the archery accuracy of fikk uny archery athletes - Nuradila, Muh Batistuta Fitoni; Prasetyo, Yudik; Prasetyo, Heru; Wibafied Billy Yachsie, Betrix Teofa Perkasa; Wibowo, Moch. Septian Resi; Nugroho, Wahyu Aji (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to reveal the physiological demands on esports athletes when competing. To achieve The purpose of this study is to determine the effect of circuit training on the archery accuracy of SELABORA Archery FIKK UNY athletes. The type of research used in this study is experimental. The research design used in this study is a “one group pretest-posttest design”. The subjects in this study are 11 SELABORA Archery FIKK UNY athletes. Data collection was carried out through archery accuracy tests before and after the training treatment. Data analysis techniques used a t-test with a significance level of 5%. Based on the results of the t-test, the calculated t-value was greater than the table t-value, indicating that the hypothesis was accepted. Therefore, it can be concluded that circuit training has an effect on the archery accuracy of SELABORA Archery FIK UNY athletes. Based on the results of the previous research and discussion, it can be concluded that the data analysis of archery accuracy above obtained a t-value (7.807) > t-table (2.28). Thus, it can be concluded that circuit training has an effect on the archery accuracy of SELABORA Archery FIKK UNY athletes.